EDUKASI PENGENALAN TEKNOLOGI INFORMASI DAN KOMPUTER PADA SISWA SDN 1 TRAYU BOYOLALI - Praningki, Tutus; Yulianto, Bagas Dwi; Anggiratih, Endang (Jurnal Pengabdian Masyarakat Polmanbabel, 2025)
The increasingly significant role of Information Technology (IT) is expected to have a positive impact on various aspects of life. Therefore, it is essential for young children to learn IT effectively. However, the lack of opportunities for children to develop their potential in using computer applications poses a barrier to enhancing their technological skills. As a concrete step, this community service program focuses on IT education for students at SD Negeri Trayu 1 Banyudono. The aim of this program is to improve students' knowledge and skills in learning computer software, particularly Microsoft Word and Microsoft PowerPoint, as well as to introduce them to computer hardware, thereby equipping them with the necessary tools to effectively utilize technology in the future.